Occurrence and risk factors for acute kidney injury in patients hospitalized with acute pyelonephritis, and their clinical outcomes: A single center study from Northern India - Saksham Seth; Nucksheeeba Aziz Bhat; Rayees Yousuf Sheikh; Puja Keshwani; Pranav Mehta (Wolters Kluwer Medknow Publications, 2023)
Background: Acute kidney injury (AKI) associated with acute pyelonephritis (APN) is considered rare. This study is conducted to find out the occurrence and risk factors for AKI in patients hospitalized with acute pyelonephritis and their clinical outcomes. Materials and Methods: All inpatients with APN from December 2018 to May 2020 were included. Results: A total of 95 patients were included. Escherichia coli was the most common organism grown. At presentation, 79/95 (83.2%) patients had renal dysfunction. 31/79 (39.2%) patients required hemodialysis. AKI was 2.4 times common in men; P = 0.013. The mean duration of fever in patients with and without renal dysfunction was 8.30 ± 2.72 and 5.31 ± 0.91 days, respectively; P < 0.001. 73/79 (92.4%) patients with AKI had anemia as against 2/14 (14.2%) patients without AKI; P < 0.001. AKI developed in 100% of the patients with known chronic kidney disease (CKD) at baseline and 41.6% of the patients with normal baseline kidney function; P < 0.001. Diabetes mellitus was present in 29/79 (36.7%) patients with AKI and 6/16 (37.5%) patients without AKI; P = 0.31. Hospital stay in days was 11.65 ± 5.9 and 5.81 ± 0.91, respectively, in patients with and without renal dysfunction; P < 0.001. 6/95 (6.3%) patients died. All six patients had renal dysfunction. At 3 months, renal functions normalized in 38/79 (48.1%) patients and 8/31 (25.8%) patients remained dialysis-dependent. Conclusions: AKI is a common complication of APN. It is usually reversible with early and appropriate management. Male gender, anemia, bilateral pyelonephritis, baseline CKD, and delayed presentation to hospital are associated with increased risk of AKI. It is associated with an increased risk of dialysis, hospitalization days, and mortality.